Pelatihan Desain Berbasis Software untuk Membantu UMKM Lokal di Desa Cadassari Kabupaten Purwakarta - Danang Purnomo; Meinawati Meinawati; Muhamad Abdul Aziz; Wida Ningsih; Elvila Junisa (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to enhance the design skills of local Micro, Small, and Medium Enterprises (MSMEs) in Cadassari Village, Purwakarta Regency, through the use of digital design software, particularly Canva and CorelDRAW. Initial needs assessment revealed that most MSME actors in the area face challenges in creating product visual identities, including logos, packaging, and promotional media. Using a participatory approach and the Community-Based Participatory Research (CBPR) method, the training program was collaboratively designed and implemented in several stages, including planning, technical training, mentoring, evaluation, and a final showcase. The results indicate a significant improvement in participants’ ability to apply design tools for their business needs, along with the emergence of collaborative learning initiatives among participants. This training program contributes to the digital empowerment of local MSMEs and serves as a replicable model for creative economy development based on community engagement.